Bearing-spesific complications of total hip arthroplasty: characterization and treatment - Mokka, Jari (Annales Universitatis Turkuensis D 1213, 2016)
Hip resurfacing arthroplasty (HRA) and large head metal-on-metal total arthroplasty (LDH MoM THA) gained popularity during the last decade. Adverse reaction to metal debris (ARMD) is a unique complication of metal bearings. ARMD is a complex reaction caused by metal debris from metal-on- metal bearing surfaces and from trunnion corrosion of modular junctions. We analyzed survivorship of 8059 LDH MoM THAs based on data of the Finnish Arthroplasty Register. We found relatively high short-term survivorship for some LDH MoM THAs, but there were remarkable differences between the devices studied. After some alarming reports of failing MoM THAs, we studied the first 80 patients who had received a ReCap-M2a-Magnum implant at our institution and evaluated the prevalence of ARMD. We found a high prevalence of pseudotumors, and, because of this, we discontinued the use of MoM bearings and followed up all patients with a MoM THA. Bone loss due infection, osteolysis or fracture poses a great challenge for reconstructive and fracture surgery. Onlay allografting for both revision and fracture surgery provides mechanical stability and increases bone stock. Bone loss and implant stability must be assessed preoperatively and adequately classified; this provides guidelines for the operative treatment of periprosthetic fractures and revision THA. In our studies on structural allografts union rates were high, although the rates of infections and dislocations were marked. In summary, early results of the use of LDH MoM devices were encouraging. However, the survival of the LDH MoMs varied. The prevalence of adverse reaction to metal debris was high after application of the ReCap-Magnum THA. New implants should be introduced carefully and under close surveillance by University clinics and arthroplasty registers.

Lonkan tekonivelen liukupinnalle tyypilliset komplikaatiot ja niiden hoito Lonkan pinnoitetekonivelen (HRA) ja isonuppisen metalli-metalli liukupintaisen tekonivelen (LDH MoM THA) käyttö yleistyi nopeasti viime vuosikymmenen aikana. Metalli--metalli liukupintoihin ja kartioliitoksiin liittyvä metallihierrekomplikaatio (adverse reaction to metal debris, ARMD) liityy lähes yksinomaan metalli-metalli liukupintoihin. Lisääntynyt tekonivelien modulaarisuus lisää metallihierrekomplikaatioiden riskiä . Tutkimuksessani analysoin 8059 LDH MoM -tekonivelen pysyvyyttä lyhyellä ja keskipitkällä aikavälillä Implanttirekisterin tietoihin perustuen. Pysyvyystulokset olivat hyviä, mutta ne vaihtelivat merkittävästi eri mallien välillä jo lyhyelläkin aikavälillä. Metalli-metalli liukupintaan liittyvien ongelmien raportoinnin yleistyessä teimme retrospektiivisen, 80 ensimmäistä implantoitua ReCap- M2a-Magnum–tekoniveltä koskevan tutkimuksen. Metallihierrekomplikaatio oli yleinen löydös, jonka seurauksena metalli-metalli liukupintaisten tekonivelten käyttö lopetettiin klinikassamme. Luukato tekonivelen ympärillä johtuu useimmiten infektiosta, osteolyysistä tai murtumasta. Periproteettisten murtumien hoito on vaativaa. Myös luunpuutos lonkan tekonivelen uusintaleikkauksissa aiheuttaa hoidollisia haasteita. Rakenteellisten luunsiirteiden paranemista koskevat tutkimustuloksemme olivat hyvät, mutta myös infektioiden ja sijoiltaanmenojen määrä oli varsin suuri. Kaiken kaikkiaan varhaiset LDH MoM tekonivelten käyttökokemukset olivat olleet rohkaisevia, mutta kaikki mallit eivät olleet pysyvyydeltään yhdenveroisia. Metalli- metalli liukupintaan ja kartioliitokseen liittyvä metallihierrekomplikaatio (ARMD) oli yleinen ReCap-Magnum-implanttia käytettäessä. Uudet implantit tulee maassamme ottaa käyttöön yliopistosairaaloiden tekonivelyksiköiden valvonnan alla. Tekonivelrekisteri on avainasemassa uusien tuotteiden arvioinnissa jo ennen kuin uusi tekonivelmalli vapautetaan laajaan käyttöön.